The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13567-018-0506-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of microRNA in mesenteric lymph nodes after Salmonella Typhimurium infection

Abstract: Salmonellosis is a gastrointestinal disease caused by non-typhoidal Salmonella serovars such as Salmonella Typhimurium. This pathology is a zoonosis, and food animals with subclinical infection constitute a vast reservoir for disease. After intestinal colonization, Salmonella Typhimurium reaches mesenteric lymph nodes (MLN), where infection is controlled avoiding systemic spread. Although the molecular basis of this infection has been extensively studied, little is known about how microRNA (miRNA) regulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…The ceRNA network of GAS5 has been reported (Liu et al, 2019;Fang et al, 2020). After literature search, we found that there were many abnormal expression of miR in mesenteric lymph nodes after ST infection (Herrera-Uribe et al, 2018). Additionally, biological website prediction, RNA pull-down and dual luciferase reporter gene assays confirmed that miR-23a has binding relation to GAS5.…”
Section: The Cerna Network Of Gas5/mir-23a/ Ptenmentioning
confidence: 72%
See 1 more Smart Citation
“…The ceRNA network of GAS5 has been reported (Liu et al, 2019;Fang et al, 2020). After literature search, we found that there were many abnormal expression of miR in mesenteric lymph nodes after ST infection (Herrera-Uribe et al, 2018). Additionally, biological website prediction, RNA pull-down and dual luciferase reporter gene assays confirmed that miR-23a has binding relation to GAS5.…”
Section: The Cerna Network Of Gas5/mir-23a/ Ptenmentioning
confidence: 72%
“…GAS5 can play a role in regulating diseases through the ceRNA mechanism. Through literature search, we found that there were many abnormal expression of miR in mesenteric lymph nodes after ST infection ( Herrera-Uribe et al, 2018 ). Therefore, we screened these miRs in the biological websites, and found miR-23a has binding relation to GAS5 ( Figure 6E ).…”
Section: Resultsmentioning
confidence: 99%
“…3b, Table S2). These mRNAs included 5 validated miR-1-3p targets ( CDC42 [30], FN1 [31], PDIA3 [32], SARS [33], and SOD1 [34]) and 27 predicted targets (based on results from the miRNA target prediction tool Targetscan 7.2) (Table S2) (35). Interestingly, we also identified CORIN itself as one of the enriched miR-1/AGO2-associated mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…This molecule is referred to as the master regulator of inflammation (Mahesh, Biswas, 2019). The high expression of miRNA-155 was reported in monocytes, macrophages, T and B lymphocytes, NK cells and DC (Dickey et al, 2017;Herrera-Uribe et al, 2018;King et al, 2016). In the above-mentioned cells, miRNA-155 is responsible for regulating the secretion of chemokines, cytokines and transcription factors in such a way that the immune response is optimal (Dickey et al, 2017).…”
Section: Key Mirnas Involved In Immune Regulationmentioning
confidence: 99%
“…Its presence in the body may lead to the development of typhoid fever or gastroenteritis (Naveed et al, 2017;Zhou et al, 2018). It is usually transmitted through food (mainly on products of animal origin contaminated with faeces) (Herrera-Uribe et al, 2018;Szewczyk et al, 2013). There are three main serotypes of Salmonella: Typhi, Typhimurium and Enteritidis (Zhou et al, 2018).…”
Section: Salmonella Typhimuriummentioning
confidence: 99%